A Roadmap to SupTech Solutions for Low Income (IDA) Countries - World Bank (World Bank, Washington, DC, 2020)
The digitalization and development of new financial products accelerated by Coronavirus 2019 (COVID-19) crisis will transform drastically the financial sector of all countries in the following years. Consequently, this will also lead to the transformation of supervisory processes, which can be greatly benefit from the support of supervisory technology (SupTech) tools. Even though there is a great potential for SupTech tools to support and enhance the supervisory processes, many supervisors are still struggling to find the right balance between functionalities, costs, and implementation approaches of SupTech tools. To support financial sector supervisors, forge their understanding and provide practical information on how to implement SupTech tools, this paper provides a step-by-step guide and use cases. The paper presents the main challenges faced by the supervisory authorities, provides different governance models used globally, and guidelines for the development of the SupTech strategy and its implementation for prudential and anti-money laundering and combating the financing of terrorism (AML and CFT) use cases.